EFEKTIVITAS GURU SEBAGAI PENDAMPING DAN PEMBERI DUKUNGAN DALAM MENGATASI BULLYING DI SEKOLAH DASAR - Wulandari, Risca; Sumartiningsih, Sri; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Abstract. This research aims to examine the effectiveness of the teacher's role as companion and support provider in overcoming bullying in elementary schools. Bullying is a serious problem that can have a negative impact on students' social and psychological development. Therefore, teachers have an important role in creating a safe and comfortable school environment for all students. This research uses a qualitative approach with a case study method in several elementary schools in the city. Data was collected through interviews with teachers, students, as well as direct observation in the classroom and school environment. The research results show that teachers play an active role in identifying bullying behavior, providing appropriate intervention, and creating open communication between students involved in bullying cases. Emotional support from teachers is also an important factor in helping victims of bullying to recover. However, the challenges faced by teachers in dealing with bullying include limited time and inadequate training regarding handling bullying. This research recommends that schools provide special training for teachers and strengthen collaboration between schools, parents and the community in overcoming the problem of bullying in elementary schools.